Caspase-3/NLRP3 signaling in the mesenchymal stromal niche regulates myeloid-biased hematopoiesis - Jing Zhang (BMC, 2021)
Abstract Background The fate of hematopoietic stem cells (HSCs) is determined by a complex regulatory network that includes both intrinsic and extrinsic signals. In the past decades, many intrinsic key molecules of HSCs have been shown to control hematopoiesis homeostasis. Non-hematopoietic niche cells also contribute to the self-renewal, quiescence, and differentiation of HSCs. Mesenchymal stromal cells (MSCs) have been identified as important components of the niche. However, the regulatory role of MSCs in hematopoiesis has not been fully understood. Methods Caspase-3 and NLRP3 gene knockout mice were generated respectively, and hematopoietic development was evaluated in the peripheral circulation and bone marrow by flow cytometry, colony formation assay, and bone marrow transplantation. Bone-associated MSCs (BA-MSCs) were then isolated from gene knockout mice, and the effect of Caspase-3/NLRP3 deficient BA-MSCs on hematopoiesis regulation was explored in vivo and ex vivo. Results We report that Caspase-3 deficient mice exhibit increased myelopoiesis and an aberrant HSC pool. Ablation of Caspase-3 in BA-MSCs regulates myeloid lineage expansion by altering the expression of hematopoietic retention cytokines, including SCF and CXCL12. Interestingly, NLRP3 gene knockout mice share phenotypic similarities with Caspase-3 deficient mice. Additionally, we found that NLRP3 may play a role in myeloid development by affecting the cell cycle and apoptosis of hematopoietic progenitors. Conclusions Our data demonstrate that the Caspase-3/NLRP3 signaling functions as an important regulator in physiological hematopoiesis, which provides new insights regarding niche signals that influence hematopoiesis regulation in the bone marrow.